Studi Empiris Pengelolaan Hutan Kota Berkelanjutan di Taman Makmur Siwalima Kota Ambon - Daoa, Bahri; Loppies, Ronny; Latuamury, Bokiraiya (Jurnal Geografi, Lingkungan dan Kesehatan, 2023)
Ambon City is the capital of Maluku Province, which is experiencing rapid growth, which can cause environmental degradation and even ecological damage. Therefore, there is a need for sustainable urban forest management as a way to increase green open space. This study aims to analyze urban forest management's technical and social aspects using rationalistic methods through interviews and observations. The assessment results of the three main criteria with assessment indicators show that the understanding of the parties related to urban forests (1168) is included in the high category (1130-1452). The results of the parties' assessment regarding the existence of urban forests based on their function (511) from the score range (368-513) and indicators of forest harmony and balance are in (score 575) from the score range (441 616), each total score is in the medium category. The results of the study technically and socially showed relatively good results. However, urban forest management towards sustainable forest development has yet to be optimally implemented sustainably.